Performance of thin blast-loaded steel plates after ballistic impact from small-arms projectiles. (March 2023) - Elveli, Benjamin Stavnar; Berstad, Torodd; Børvik, Tore; Aune, Vegard
Abstract: It is known from real blast-load events that the combined effect of fragment impact and blast loading is more severe than the effect of the blast loading alone. The present study investigates this effect by comparing the blast response of thin steel plates pre-damaged by either ballistic impacts or idealized pre-cut circular holes under similar blast loading conditions. The ballistic impacts were performed with a rifle, firing 7.62 mm APM2 projectiles, and the subsequent blast loading was applied in a shock tube facility. During the blast tests, pressure measurements and two high-speed cameras were used to record the dynamic response of the target plates and allowed for a reliable experimental procedure. To investigate the strength-ductility trade-off dilemma of the material during extreme loading, three different steels with different levels of strength and ductility were used in the tests. Numerical simulations were conducted in an attempt to obtain more insight into the fracture characteristics of the plates. For similar loading conditions and material, the target plates exposed to ballistic impact showed a reduced resistance to fracture during blast loading compared with target plates containing pre-formed circular holes. As for the effect of material strength and ductility, the global deformation decreased, while the localization of plasticity increased, with an increased material strength. The fracture resistance was also observed to decrease with increased material strength. The numerical models were able to capture the main trends observed in the physical tests, i.e., a decrease in fracture resistance with initial ballistic impact, and a reduction in fracture resistance with increased material strength. The numerically predicted crack paths also showed a strong dependence upon the initial cracks caused by the petals from the ballistic impacts. Highlights: Thin, pre-damaged steel plates were subjected to blast loading. Pre-damage from either ballistic impacts or pre-cut circular holes. Ballistic impacts more detrimental for blast resistance than pre-cut holes. A restart analysis was used to simulate ballistic impact before blast loading. Petalling cracks played a crucial role in simulating the blast resistance.